Study of indium tin oxide thin films deposited on acrylics substrates by Ion beam assisted deposition technique - Meng Lijian (2009)
Indium tin oxide (ITO) thin films have been deposited onto acrylics (PMMA) substrates by ion beam assisted deposition technique at different oxygen flows. The structural, optical and electrical properties of the deposited films have been characterized by X-ray diffraction, transmittance, FTIR, ellipometry and Hall effect measurements. The optical constants of the deposited films have been calculated by fitting the ellipsometric spectra. The effects of the oxygen flow on the properties of the deposited films have been studied. It has been found that 40 sccm oxygen flow is an optimum value for getting the films with good transmittance and low electrical resistivity.